SAS4P: Providing automatic smoking detection for a persuasive smoking cessation application - Pedro O Rossel; Lorenzo Paredes; Antonio Bascur; Claudia Martínez-Carrasco; Valeria Herskovic (International Journal of Distributed Sensor Networks)
Smoking is the biggest avoidable health risk, causing millions of deaths per year worldwide. Persuasive applications are those designed to change a person’s behavior, usually in a specific way. Several mobile phone applications and messaging systems have been used to promote smoking cessation. However, most interventions use participants’ self-reports to track cigarette consumption and avoidance, which may not be accurate or objective. Previous proposals have used sensors to track hand movements and other contextual data to detect smoking or have used devices to detect smoke or breath carbon monoxide. This article proposes a low-cost wearable device that may be worn in a front shirt pocket or clipped to clothing to detect smoke and secondhand smoke. Furthermore, the device is integrated into a persuasive application to promote smoking cessation. The device was evaluated through an experiment to detect whether it may detect direct, passive, and no smoking conditions. The results are promising and may help improve tracking of cigarettes in persuasive applications.